2007
DOI: 10.1080/00220380701259723
|View full text |Cite
|
Sign up to set email alerts
|

Productivity growth of East Asia economies' manufacturing: A decomposition analysis

Abstract: Applying a stochastic production frontier to sector-level data within manufacturing, this paper examines total factor productivity (TFP) growth for seven East Asian economies during 1963-98, using both single country and cross-country regressions. The analysis focuses on the trend in technological progress (TP) and technical efficiency change (TEC), and the role of productivity change in economic growth. The empirical results reveal that although input factor accumulation is still the main source for East Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Assimilationists argued that the answer to growth lies in the use of more efficient technology, represented by World Bank (1993), Sarel (1996Sarel ( , 1997, Nelson & Pack (1999). Liao et al (2007) concluded that Krugman's (1994) hypothesis that the fast growth of East Asian economies had little to do with TFP growth was invalid, but could not dispute Young's (1995) 's conclusion that these economies' growth had been mainly input-driven.…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assimilationists argued that the answer to growth lies in the use of more efficient technology, represented by World Bank (1993), Sarel (1996Sarel ( , 1997, Nelson & Pack (1999). Liao et al (2007) concluded that Krugman's (1994) hypothesis that the fast growth of East Asian economies had little to do with TFP growth was invalid, but could not dispute Young's (1995) 's conclusion that these economies' growth had been mainly input-driven.…”
Section: Model Resultsmentioning
confidence: 99%
“…This mirrors a debate that featured strongly in the research on growth performance during the years of the so-called Asian miracle and tiger economies. Liao et al (2007) identified two sides of the debate. Accumulationists believed that the increased use and accumulation of inputs (especially the investment) rather than the increases in productivity explains all growth; this was represented by Young (1992Young ( , 1994aYoung ( , 1994bYoung ( , 1995, Krugman (1994), Collins & Bosworth (1996), Drysdale & Huang (1997), Crafts (1999a, 1999b.…”
Section: Model Resultsmentioning
confidence: 99%
“…We are aware of the efforts of some researchers (e.g., Mahadevan, 2000;Liao et al, 2007) who attempted to do so. But, in our view, TFP cannot be decomposed into these two measures quantitatively.…”
Section: Effects Of Output Growth and Time Dependent Technology On Tfmentioning
confidence: 99%
“…27 The software can produce the convergence characteristics of the proposed NN model which shows the MSE history (decreasing curve) over iterations in the training process. 28 See Wong (2003) Liao et al (2007) reported that while both the Cobb-Douglas and translog formulations provide positive production elasticities showing no or little violations of monotonicity, the Cobb-Douglas formulation is the only one to fulfil the regularity condition of concavity. 30 As pointed out by one referee, input congestion can be dealt with by decomposing the technical efficiency scores calculated from a CRS DEA into congestion inefficiency, scale inefficiency and 'pure' technical efficiency.…”
Section: Discussionmentioning
confidence: 99%